Tyroviruses are a new group of temperate phages that infect Bacillus species in soil environments worldwide - Steven Batinovic; Cassandra R. Stanton; Daniel T. F. Rice; Brittany Rowe; Michael Beer; Steve Petrovski (BMC Genomics, 2022)
Abstract Background Bacteriophages are widely considered to be highly abundant and genetically diverse, with their role in the evolution and virulence of many pathogens becoming increasingly clear. Less attention has been paid on phages preying on Bacillus, despite the potential for some of its members, such as Bacillus anthracis, to cause serious human disease. Results We have isolated five phages infecting the causative agent of anthrax, Bacillus anthracis. Using modern phylogenetic approaches we place these five new Bacillus phages, as well as 21 similar phage genomes retrieved from publicly available databases and metagenomic datasets into the Tyrovirus group, a newly proposed group named so due to the conservation of three distinct tyrosine recombinases. Genomic analysis of these large phages (~ 160–170 kb) reveals their DNA packaging mechanism and genomic features contributing to virion morphogenesis, host cell lysis and phage DNA replication processes. Analysis of the three tyrosine recombinases suggest Tyroviruses undergo a prophage lifecycle that may involve both host integration and plasmid stages. Further we show that Tyroviruses rely on divergent invasion mechanisms, with a subset requiring host S-layer for infection. Conclusions Ultimately, we expand upon our understanding on the classification, phylogeny, and genomic organisation of a new and substantial phage group that prey on critically relevant Bacillus species. In an era characterised by a rapidly evolving landscape of phage genomics the deposition of future Tyroviruses will allow the further unravelling of the global spread and evolutionary history of these Bacillus phages.